2010
DOI: 10.1007/jhep10(2010)038
|View full text |Cite
|
Sign up to set email alerts
|

Measuring V ub and probing SUSY with double ratios of purely leptonic decays of B and D mesons

Abstract: The experimental prospects for precise measurements of the leptonic decays B u → τ ν/µν, B s → µ + µ − , D → µν and D s → µν/τ ν are very promising. Double ratios involving four of these decays can be defined in which the dependence on the values of the decay constants is essentially eliminated, thus enabling complementary measurements of the CKM matrix element V ub with a small theoretical error. We quantify the experimental error in a possible future measurement of |V ub | using this approach, and show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 92 publications
1
13
0
Order By: Relevance
“…We use the following 95% C.L. intervals, which include theoretical and experimental uncertainties [15,47,48]:…”
Section: Constraintsmentioning
confidence: 99%
“…We use the following 95% C.L. intervals, which include theoretical and experimental uncertainties [15,47,48]:…”
Section: Constraintsmentioning
confidence: 99%
“…A comparison of the constraints on specific SUSY models from the double ratio and from BR(B s → µ + µ − ) alone is of much interest because the theoretical input parameters |V ub | and f Bs for these two observables are independent. Such a comparative study was performed for the first time in [21], and it was shown that the double ratio can provide stronger constraints. In particular, the constraints from the double ratio are maximised (minimised) for smaller (larger) |V ub |, while the constraints from BR(B s → µ + µ − ) are maximised (minimised) for larger (smaller) f Bs .…”
Section: The Double Ratios Of Purely Leptonic Decaysmentioning
confidence: 99%
“…Moreover, we consider an alternative observable which includes BR(B s → µ + µ − ), namely, a double ratio of leptonic decays [19,20]. The double ratio has no dependence on the absolute value of the decay constant f Bs , which is the main source of uncertainty in the SM prediction for BR(B s → µ + µ − ), and it was shown in [21] that this observable can provide competitive (or even superior) constraints on the SUSY parameter space. The main uncertainty in the SM prediction for the double ratio arises from the CKM matrix element |V ub |, for which the prospects of precise measurements at high-luminosity B factories are very promising.…”
Section: Introductionmentioning
confidence: 99%
“…and D s ! =, it could be possible to enhance the sensitivity of the individual decays, through the cancellation of hadronic uncertainties, and stronger constraints can be obtained [13,16].…”
mentioning
confidence: 99%